2020
DOI: 10.1021/acs.orglett.0c03433
|View full text |Cite
|
Sign up to set email alerts
|

Rh-Catalyzed Asymmetric Hydroaminomethylation of α-Substituted Acrylamides: Application in the Synthesis of RWAY

Abstract: The successful rhodium-catalyzed asymmetric hydroformylation and hydroaminomethylation of α-substituted acrylamides is described using 1,3-phosphite-phosphoramidite ligands based on a sugar backbone. A broad scope of chiral aldehydes and amines were afforded in high yields and excellent enantioselectivities (up to 99%). Furthermore, the synthetic potential of this method is demonstrated by the single-step synthesis of the brain imaging molecule RWAY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Only two existing publications reporting the AHF of α-substituted acrylamides appeared in 2020. 120,123 Godard et al reported the first use of 1,3-phosphite-phosphoramidite ligands based on a sugar backbone derived from D-xylose in AHF of α-substituted acrylamides (L13, Scheme 42). The best catalytic performance was obtained with ligands bearing a bulky group on nitrogen atom (R= Cy and R= (S)-CHMePh) and a (S ax ,S ax )-biaryl moiety (Scheme 42).…”
Section: N-selective Asymmetric Hydroformylationmentioning
confidence: 99%
“…Only two existing publications reporting the AHF of α-substituted acrylamides appeared in 2020. 120,123 Godard et al reported the first use of 1,3-phosphite-phosphoramidite ligands based on a sugar backbone derived from D-xylose in AHF of α-substituted acrylamides (L13, Scheme 42). The best catalytic performance was obtained with ligands bearing a bulky group on nitrogen atom (R= Cy and R= (S)-CHMePh) and a (S ax ,S ax )-biaryl moiety (Scheme 42).…”
Section: N-selective Asymmetric Hydroformylationmentioning
confidence: 99%
“…The hemiacetal reaction via PCC/ Et 3 N one-pot method afforded bridged [2,2,1]bicyclic lactones in high yield (up to 95 %) and excellent enantioselectivity (Scheme 22f). [59] Sugar backbone ligands were also applied to phosphoramidite ligands, Godard [60] et al synthesized a sugar-backbone phosphoramidite ligand L18 for the rhodium-catalyzed asymmetric hydroformylation and hydroaminomethylation of αsubstituted acrylamides. The ee value of the chiral aldehyde product was as high as 99 %, and the ee value of the chiral amine product was up to 86 %.…”
Section: Binol-phosphoramidite Ligandsmentioning
confidence: 99%
“…Sugar backbone ligands were also applied to phosphoramidite ligands, Godard [60] et al. synthesized a sugar‐backbone phosphoramidite ligand L18 for the rhodium‐catalyzed asymmetric hydroformylation and hydroaminomethylation of α‐substituted acrylamides.…”
Section: Phosphoramidite Ligandsmentioning
confidence: 99%
“…Indeed, only a few examples were reported in the asymmetric hydroformylation of nonsubstituted acrylamides with moderate yields and enantioselectivities (18). The only two existing publications reporting the AHF of α-substituted acrylamides appeared in 2020 (15,19). In one of them, only three substrates were studied.…”
Section: N-selective Asymmetric Hydroformylationmentioning
confidence: 99%
“…Their modularity was key to achieve the best catalytic performance, being ligands with a bulky N-group and an (S ax , S ax )-biaryl moiety the ones that provided the best results (R ¼ Cy and R ¼ (S)-CHMePh) (Scheme 9). With the optimal ligands, it was possible to hydroformylate for the first time a broad range of acrylamides with different substituents at the α-position and on the amide group with high-to-excellent enantioselectivities (74-99% ee) and good-to-high yields (50-87%) (19). Furthermore, hydroformylation reactions could be performed at 60 °C.…”
Section: N-selective Asymmetric Hydroformylationmentioning
confidence: 99%